2006
DOI: 10.1098/rspb.2006.3671
|View full text |Cite
|
Sign up to set email alerts
|

Global phylogeographic limits of Hawaii's avian malaria

Abstract: The introduction of avian malaria (Plasmodium relictum) to Hawaii has provided a model system for studying the influence of exotic disease on naive host populations. Little is known, however, about the origin or the genetic variation of Hawaii's malaria and traditional classification methods have confounded attempts to place the parasite within a global ecological and evolutionary context. Using fragments of the parasite mitochondrial gene cytochrome b and the nuclear gene dihydrofolate reductase-thymidylate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
222
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 223 publications
(233 citation statements)
references
References 32 publications
9
222
1
1
Order By: Relevance
“…Furthermore, Tern Island includes haematophagous flies (Hippoboscidae) that can serve as vectors of disease [68,69]. Whether vector-transmitted diseases have strong fitness consequences in frigatebirds is still unresolved, with Haemosporidian parasites causing severe health problems in some host-parasite systems but not others [70].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Tern Island includes haematophagous flies (Hippoboscidae) that can serve as vectors of disease [68,69]. Whether vector-transmitted diseases have strong fitness consequences in frigatebirds is still unresolved, with Haemosporidian parasites causing severe health problems in some host-parasite systems but not others [70].…”
Section: Discussionmentioning
confidence: 99%
“…Among parasites, the Hawaiian form of malaria is the only lineage of malaria parasite that appears to be common among passerines of French Polynesia (Beadell et al 2006). In a survey of birds on Moorea, Society Islands, this parasite lineage was seen at low frequency in several introduced species (no data on native species owing to their rarity).…”
Section: Recent Impactsmentioning
confidence: 99%
“…During the last ten years, the amplification of a specific part of the mitochondrial cytochrome b (cyt b) gene (Bensch et al 2000, Perkins and Schall 2002) has provided new opportunities in the studies of specificity, diversity, distribution, ecology and various aspects of phylogeny and evolution of avian haemosporidian parasites (Bensch et al 2000, Waldenström et al 2002, Beadell et al 2004, Fallon et al 2005. Recent papers have demonstrated that the diversity of cyt b lineages is much greater than that of the described morphospecies (Perkins and Schall 2002;Ricklefs and Fallon 2002;Waldenström et al 2002;Beadell et al 2004Beadell et al , 2006Bensch et al 2004;PĂ©rez-Tris and Bensch 2005;Szymanski and Lovette 2005;ValkiĆ«nas 2005). These studies suggest that many of the genetic lineages may represent distinct evolutionary entities .…”
Section: Introductionmentioning
confidence: 99%